The role of d-galactose in the aging heart and brain - Cherry Bo-Htay (2020)
© 2019 Elsevier Inc. All rights reserved. Aging is an inevitable, complex biological process caused by a variety of factors including both genetic and environmental influences. It is one of the prime risk factors for the advancement of many pathological conditions such as cardiovascular diseases and neurodegenerative disorders. Numerous animal models have been used to add to our understanding of the aging process, to inform therapeutic interventions, and to limit the aging effects on various organs. Of these models the d-galactose-induced aging model is the most commonly used as a mimetic aging model. Despite the frequent use of this model, actually, how d-galactose accelerates cardiac and brain aging remains unclear. Currently, hyperbaric oxygen therapy (HBOT) is used to treat neurodegeneration and brain injury. This chapter comprehensively summarizes recent results from d-galactose treatment in both in vitro and in vivo cardiac and brain aging experiments and the different aspects of therapeutic interventions, in particular HBOT.